Nuremberg and Group Prosecution - Richard Arens (Washington University Law Quarterly, 1951)
The trial of the Nazi war criminals at Nuremberg for crimes against peace, war crimes and crimes against humanity involved not only the indictment of individual defendants but also the indictment of the major Nazi organizations. An aspect almost completely ignored in the welter of allegations concerning the ex post facto basis of the Nuremberg prosecutions is that concerning the infliction of collective or group sanctions through adjudication of group criminality. The issue as to whether the use of group sanctions at Nuremberg was acceptable under democratic standards and as to whether it provided impetus or incentive for duplication on these shores embodies the central point of investigation.
Keywords: War and emergency powers